Microbial oncogenesis within the gastric niche: how the gastric microbiota influences H. pylori-induced disease progression - Lowe, MaKayla S.; Peek, Richard M. (Frontiers in Microbiology, 2025)
Chronic pathogens incur a significant public health burden, contributing to the development of 1 in 5 cancer cases worldwide. Helicobacter pylori, a Gram-negative bacterium that colonizes the gastric mucosa, is the strongest known risk factor for gastric adenocarcinoma, the fifth leading cause of cancer-related mortality. H. pylori colonizes almost half of the world's population; however, despite its high prevalence, only approximately 1-3% of infected individuals progress to this malignancy. These data suggest that H. pylori colonization alone may be insufficient to fully drive oncogenic progression. Previously considered a sterile environment, the stomach is now recognized to harbor a diverse microbial ecosystem, which plays a crucial role in human health and disease. Emerging research highlights the complex interplay between H. pylori and the gastric microbiota, with several commensal bacterial species now identified as modulators of disease progression. Clinical data have defined key variations in gastric microbiota composition between H. pylori-infected individuals who progress toward gastric cancer and those who simply develop gastritis alone, further suggesting that the gastric microbiota affects cancer risk in synergy with H. pylori. In this review, we will discuss microbial species identified within the stomach of H. pylori-infected persons that orchestrate detrimental or protective interactions, which influence the host response and alter cancer risk.